2020
DOI: 10.1080/23802359.2020.1839366
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Ricania speculum (Walker, 1851) (Hemiptera: Ricaniidae): investigation of intraspecific variations on mitochondrial genome

Abstract: We have determined a mitochondrial genome of Ricania speculum (Walker, 1851) collected in Jeollabuk-do, Republic of Korea. The circular mitogenome of R. speculum is 15,530 bp long which is shorter than that of the previous mitogenome of R. speculum by 199 bp. It includes 13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNAs. Intraspecific variation between two mitogenome of R. speculum was investigated: 171 SNPs and 18 INDELs were identified, presenting a high level of intraspecific variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…This result suggests that next-generation sequencing technology that provides a large number of short reads can be used to provide evidence for the existence of endosymbiont species using DNA extracted from insect species. These results draw comparison to previous studies that have successfully identified a multiple number of complete organelle or bacterial genomes from one NGS library [12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…This result suggests that next-generation sequencing technology that provides a large number of short reads can be used to provide evidence for the existence of endosymbiont species using DNA extracted from insect species. These results draw comparison to previous studies that have successfully identified a multiple number of complete organelle or bacterial genomes from one NGS library [12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionsupporting
confidence: 65%
“…This suggests that these insect-hosted fungal endosymbionts have been evolved independently from the other fungal species in the Ophiocordycipitaceae family. Owing to the advantages of NGS raw reads, which can detect sequences from unknown or unexpected organisms [12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], we successfully identified the complete mitogenomes of WBPH fungal endosymbionts within the NGS raw reads, suggesting that we can understand their phylogenetic positions of fungal symbiont with high resolution without the need to isolate the symbiont from the host. Furthermore, our study shows that NGS raw reads of insects generated in the future can be used to pinpoint further fungal endosymbionts that have previously been difficult to identify.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pair-wise sequence alignments among complete mitogenome of WBPH including the mitogenome sequenced in this study were conducted by MAFFT v7.450 [56] with the default option. Identifying intraspecific variations, SNPs and INDELs, on the WBPH mitogenomes was conducted using the function, 'Find variations/SNPs,' implemented in the Geneious Prime ® v2020.2.4 (Biomatters Ltd., Auckland, New Zealand), which has been utilized in the previous insect mitochondrial genome studies [37,[57][58][59][60][61][62][63][64]. When the number of INDELs was calculated, continuous INDEL bases were considered one INDEL region.…”
Section: Identification Of Intraspecific Variations Of Wbph Mitogenomesmentioning
confidence: 99%
“…Because of the short length of NGS raw reads, especially those generated by the Illumina HiSeq platform (36 bp-151 bp) [28], the minimum depth for assembly is relatively high, for example, average 30× coverage for human genome resequencing [29], in comparison to that of the Sanger sequencing method: 6×-10× depth for de novo assembly [30,31]. Interestingly, this high coverage of NGS raw reads provides a deep profile of each base of the assembled mitochondrial genomes [32][33][34][35][36][37][38], usually because the amount of mitochondrial genomic DNA in a cell is much higher than that of the main chromosomes. This deep profile can provide the polymorphic bases that display more than one nucleotide in a specific position of the mitochondrial genome.…”
Section: Introductionmentioning
confidence: 99%